Sustainable valorization of water hyacinth waste pollutant via pyrolysis for advance microbial fuel investigation - Pal D.B.; Tiwari A.K.; Prasad N.; Syed A.; Bahkali A.H.; Srivastava N.; Singh R.P.; Gupta V.K. (My University, 2025)
Present study has been focused on the bio-energy potential of waste biomass (water hyacinth leaves and its stem). Pyrolysis of both biomasses were investigated at five different heating rates (5–25 °C/min) using thermogravimetric analyzer. For both biomasses, maximum thermal degradation occurred within the temperature range of 200–400 °C, which is the active pyrolytic zone. Three non-iso-conversional (degradation models) including the Kissinger-Akahira-Sunose, Flynn-Wall-Ozawa, and Starink were used to calculate the activation energy of both biomasses. The activation energy was around 92–98 kJ/mol for water hyacinth leaves and 151–153 kJ/mol for water hyacinth stems. The results suggest that these low-cost abundantly available biomasses have a good potential for the production of solid bio-fuel. © 2022 Elsevier Ltd